Wisata Religi Sebagai Ruang Perjumpaan Budaya di Gereja Graha Maria Annai Velangkanni Kecamatan Medan Tuntungan (Studi Kasus Fenomenologis di Gereja Graha Maria Annai Velangkanni di Kecamatan Medan Tuntungan) - Sri Wulandari (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the Graha Maria Annai Velangkanni Church in Medan Tuntungan as a religious tourism site that integrates spirituality and cultural encounters within a multireligious society. Using a qualitative approach with a phenomenological method, this research explores visitors’ subjective experiences through observations, in-depth interviews, and field documentation. The findings reveal that the church’s unique architecture inspired by South Indian design, its inclusive religious symbols, and its sacred yet open atmosphere create a universal and peaceful spiritual experience. Non-Catholic visitors, including Muslims, expressed feelings of serenity, acceptance, and admiration for the cultural harmony embodied by the church. Social interactions among visitors and the surrounding community demonstrate the presence of natural cultural dialogue without conflict, indicating that the church functions as a social bridge that strengthens tolerance and social cohesion. This study concludes that Annai Velangkanni is not only a place of worship but also an educational and cultural space that embodies the values of multiculturalism. These findings contribute to the development of inclusive and harmonious religious tourism that promotes interfaith dialogue in Indonesia.